2018
DOI: 10.37236/7512
|View full text |Cite
|
Sign up to set email alerts
|

On Graphs whose Flow Polynomials have Real Roots Only

Abstract: Let G be a bridgeless graph. In 2011 Kung and Royle showed that all roots of the flow polynomial F (G, λ) of G are integers if and only if G is the dual of a chordal and plane graph. In this article, we study whether a bridgeless graph G for which F (G, λ) has real roots only must be the dual of some chordal and plane graph. We conclude that the answer of this problem for G is positive if and only if F (G, λ) does not have any real root in the interval (1, 2). We also prove that for any non-separable and 3-edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Problem asks if scriptGRgoodbreakinfix=scriptGI holds. Dong obtained the following results on the study of Problem .…”
Section: Graphs With Real Flow Roots Onlymentioning
confidence: 96%
See 2 more Smart Citations
“…Problem asks if scriptGRgoodbreakinfix=scriptGI holds. Dong obtained the following results on the study of Problem .…”
Section: Graphs With Real Flow Roots Onlymentioning
confidence: 96%
“…By Lemmas and , to study Problem , it suffices to consider 3‐edge connected non‐separable graphs in scriptGR which do not contain any proper 3‐edge‐cut. Dong also showed that if G is such a graph in scriptGRgoodbreakinfix−scriptGI, then W(G)goodbreakinfix≥3 and G contains at least f(W(G)) flow roots in (1,2), where f(k) has values 9goodbreakinfix,11goodbreakinfix,14, respectively, for kgoodbreakinfix=3goodbreakinfix,4goodbreakinfix,5 and f(k)goodbreakinfix=27k112722 for all integers kgoodbreakinfix≥6.…”
Section: Graphs With Real Flow Roots Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…(v) Theorem 4.6 (Dong [8]) For any bridgeless graph G, if F (G, x) has real roots only, then either all roots of F (G, x) are integral or F (G, x) has at least 9 roots in (1, 2).…”
Section: Tutte's 3-flow Conjecture [1970s]mentioning
confidence: 99%
“…(iv) Conjecture 4.4 (Dong [8,10]) For any bridgeless graph G, if F (G, q) has real roots only, then all roots of F (G, q) are integral.…”
Section: Tutte's 3-flow Conjecture [1970s]mentioning
confidence: 99%